Postvaginal Delivery Caecal Volvulus and Perforation - M. M. Abdullah Agha (Case Reports in Obstetrics and Gynecology)
Intestinal obstruction is an uncommon complication of pregnancy and pueperium. It has different etiologies and voluvlus is one of the common causes. High index of suspicion is needed to diagnose it as initial presentation is nonspecific and that is critical to avoid adverse outcomes. We presented here one of these cases that followed vaginal delivery and ended with caecal perforation and hemicolectomy.